Gestão eficiente de água e energia em prédios públicos: estudo de caso da Escola Superior de Sargentos - Souza Filho, Antonio Alves (2018)
In a corporate world the increase in profitability permeates by effective actions in relation to the prevention and reduction of waste. In 2016 the Energy Research Company (Empresa de Pesquisa Energética) - EPE data showed that the public sector presented an average energy consumption annual growth rate of 2.3% per year in 20 years, being equivalent to the industry rate, but without the public sector realizing the manufacture of any product and, above, still, the residential and agricultural sectors in the same period, intensifying the issue of efficiency in the management of financial resources in the public sector and leading to question the level of waste. The objective of this study is based on analyze technologies as a means to make public buildings used by the São Paulo Military Police Corporation - PMESP more sustainable, aimed at delivering the results with better efficiency in the consumption of water and energy, minimizing waste, using qualitative methodology with some case study, bibliographical review and structured research application, in order to understand the barriers and lever for the implantation of environmental technologies in public buildings in São Paulo State , maintaining its routine activities, with management more efficiency, focused on energy and water consumptions. The Senior Sergeant School - ESSgt (Escola Superior de Sargentos), located at 750, Condessa Elizabeth de Robiano Avenue, São Paulo-SP, in Brazil, was elected for this case study in particular, because it was a pioneer in environmental and quality certification, providing an environment of greater adherence to this study and the establishment of standards with guidelines for the bidding of the technologies, spreading to other public buildings. Regarding the environmental gains, it was concluded that the energy efficiency and the more efficient use of the water resource observed, can ensure economic and eco-efficient return.